Sicily and the Mediterranean in the Middle Ages - Takayama, Hiroshi, 1947- author.
1 online resource (xx, 393 pages).
Keywords: “This book is a collection of milestone articles of a leading scholar in the study of the Norman Kingdom of Sicily, a crossroads of Latin-Christian, Greek-Byzantine, and Arab-Islamic cultures and one of the most fascinating but also one of the most neglected kingdoms in the medieval world. Some of his articles were published in influential journals such as English Historical Review, Viator, Mediterranean Historical Review, and Papers of the British School at Rome, while others appeared in hard-to-obtain festschrifts, proceedings of international conferences, and so on. The articles included here, based on analysis of Latin, Greek, and Arabic documents as well as multi-lingual parchments, explore subjects of interest in medieval Mediterranean world such as Norman administrations, multi-cultural courts, Christian-Muslim diplomacy, conquests and migrations, religious tolerance and conflicts, cross-cultural contacts, and so forth. Some of them dig deep into curious specific topics, while others settle disputes among scholars and correct our antiquated interpretations. His attention to the administrative structure of the kingdom of Sicily, whose bureaucracy was staffed by Greeks, Muslims and Latins, has been a particularly important part of his work, where he has engaged in major debates with other scholars in the field“--